Automatic Cat Feeding And Monitoring System In Hiro Catshop Shop Based On The Internet Of Things - Daulay, Nelly Khairani (ADPEBI, 2022)
Cat feeding is still done manually without a system and there is no monitoring system for cat food leftovers that can be accessed through the website, Build a Monitoring System and Automatic Cat Feeder at Hiro CatShop Based on the Internet Of Things (IoT) that can monitor and provide food cat automatically and can be accessed remotely via the Website. The method that the author uses in conducting this research is a qualitative research method. Qualitative research methods seek an understanding of meaning, understanding, reality, events, or life by being directly and/or indirectly involved in the environment under study. cat in place, DHT11 sensor as a temperature detector in the room around the cat food place, servo motor as a means of opening the lid for cat food that comes out according to a predetermined schedule, NodeMCU to read and send sensor data into the database With an automatic cat feeding monitoring system this will make it easier for shop owners or shop employees to monitor cat feeding through the website, shop owners don't need to be afraid anymore if it's too late to feed the cat and waste too much time to come to the cat feeding place and also don't need to be afraid of losing n data caused by lost records (human error).